Analisis Cluster Pengelompokan Kepribadian Warga Binaan Pemasyarakatan di Era Revolusi Industri 4.0 - Kusumawati, Retno Ryani; Hannibal, Hannibal; Asih, Retika Najmamulat (Universitas PGRI Yogyakarta, 2019)
Industrial revolution 4.0 has affected all fields, including Indonesian Ministry of Law and Human Rights whose conducting a revitalization of correctional service where capacity was the main point of clustering is now changing into clustering based on change in behavior of the prisoners, which then used as recommendation for placing prisoners into Minimum Security, Medium Security and Maximum Security Prison. Prisoner’s Personality will show a prisoner’s tendency to behave and to think. Personality can be measured through Big Five Personality Model consisting of Openness to Experience, Concientiousness, Extraversion, Agreeableness and Neuroticism. To simplify the placement process, the K-Means Clustering method is used. Of 137 prisoners assessed from Rangkasbitung and Serang Prison, 27 prisoners being placed to Medium Security prison, 52 prisoners to Maximum Security prison, and 58 prisoners to Minimum Security prison.